Functions of Vγ4 T Cells and Dendritic Epidermal T Cells on Skin Wound Healing - Li, Yashu; Wu, Jun; Luo, Gaoxing; He, Weifeng (Frontiers in Immunology, 2018)
Wound healing is a complex and dynamic process that progresses through the distinct phases of hemostasis, inflammation, proliferation, and remodeling. Both inflammation and re-epithelialization, in which skin γδ T cells are heavily involved, are required for efficient skin wound healing. Dendritic epidermal T cells (DETCs), which reside in murine epidermis, are activated to secrete epidermal cell growth factors, such as IGF-1 and KGF-1/2, to promote re-epithelialization after skin injury. Epidermal IL-15 is not only required for DETC homeostasis in the intact epidermis, but it also facilitates the activation and IGF-1 production of DETC after skin injury. Further, the epidermal expression of IL-15 and IGF-1 constitutes a feedback regulatory loop to promote wound repair. Dermis-resident Vγ4 T cells infiltrate into the epidermis at the wound edges through the CCR6-CCL20 pathway after skin injury and provide a major source of IL-17A, which enhances the production of IL-1β and IL-23 in the epidermis to form a positive feedback loop for the initiation and amplification of local inflammation at the early stages of wound healing. IL-1β and IL-23 suppress the production of IGF-1 by DETCs and therefore impede wound healing. A functional loop may exist among Vγ4 T cells, epidermal cells, and DETCs to regulate wound repair.